Vegetation Fires and Pollution in Asia - Vadrevu, Krishna Prasad; Ohara, Toshimasa; Justice, Chris (Cham : Springer International Publishing : Imprint: Springer, 2023)
Vegetation fires are prevalent in several regions of the world, including South/ Southeast Asia (S/SEA). Fire occurrence and spread are influenced by fuel type, topography, climate, weather, and lightning, among others. In S/SEA, human-initiated fires are responsible for most of the incidents in addition to natural factors. Through biomass burning, vegetation fires can emit large quantities of greenhouse gases and air pollutants such as CO2, CO, NOx, CH4, non-methane hydrocarbons, and other chemical species, including aerosols that can affect air quality and health at both local and regional scales. Moreover, biomass burning pollutants can travel long distances and impact regional climate. Therefore, quantifying vegetation fires and their impacts is critical at different spatial scales. This book includes contributions from renowned researchers from the USA and South/ Southeast Asia on various fire-related topics. The contributions resulted from several international meetings and workshops organized in Asia as part of the South/ Southeast Asia Research Initiative (SARI) under the NASA Land-Cover/Land-Use Change Program. The book is divided into three sections, each containing multiple contributions: a) Mapping, Monitoring, and Modeling of Vegetation Fires, b) Greenhouse Gas Emissions and Air Pollution, and c) Air Pollution Modeling and Decision Support Systems. These sections are preceded by an introductory chapter by the editors that highlights the latest satellite-derived fire statistics and the current fire situation in S/SEA. This book will be a valuable resource for remote sensing scientists, geographers, ecologists, atmospheric, climate, environmental scientists, including policymakers, and all who wish to advance their knowledge on vegetation fires and emissions in South/Southeast Asia.
1. Vegetation Fires and Biomass Burning in South/Southeast Asia - An Overview -- Section I: Mapping , Monitoring and Modeling of Vegetation Fires -- 2. Wildfire monitoring using infrared bands and spatial resolution effects -- 3. Status and Drivers of Forest Fires in Myanmar -- 4. Vegetation Fires and Entropy Variations In Myanmar -- 5. Crop residue burning and forest fire emissions in Nepal -- 6. Firewood Burning Dynamics by the Sri Lankan Households: Trends, Patterns, and Implications -- 7. Burnt Area Signal Variations in Agriculture and Forested Landscapes of India - A Case Study Using Sentinel A/B Synthetic Aperture Radar -- 8. Application of Interferometry SAR for Monitoring of Peatland Areas- Case Studies in Indonesia -- 9. Active Fire Monitoring of Thailand and Upper ASEAN by Earth Observation Data: benefits, lessons learned and what still needs to be known -- 10. Detecting Vegetation Regrowth after Fires in Small Watershed Settings Using Remotely Sensed Data and Local Community Participation Approach -- 11. Long-Term Spatiotemporal Distribution of Fire over Maritime Continent and their Responses to Climate Anomalies -- 12. Vegetation Fires in Laos - An Overview -- 13. Vegetation Fires, Fire Radiative Power and Intermediate Fire Occurrence Intensity (IFOI) Hypothesis Testing in Myanmar, Laos and Cambodia -- 14. Analyzing fire behavior and calibrating a fire growth model in a seasonal dry tropical forest area -- Section II: Greenhouse Gas Emissions and Air Pollution -- 15. Spatiotemporally resolved pollutant emissions from biomass burning in Asia -- 16. Twenty-year variations of aerosol optical depth over Asia in relation to anthropogenic and biomass burning emissions -- 17. Light Absorption Properties of Biomass Burning Emissions in Bangladesh: Current State of Knowledge -- 18. Remote Sensing of greenhouse gases and aerosols from agricultural residue burning over Pakistan -- 19. A comparative study of energy, emissions and economic efficiency of various cookstoves in Nepal -- 20. Estimation of Ultrafine Particulate Matter Emissions from Biomass Burning Using Satellite Imaging and Burn Severity -- 21. Characteristics of Transboundary Haze and General Aerosol over Pulau Pinang, Malaysia -- 22. Measurements of atmospheric carbon dioxide emissions from fire-prone peatlands in Central Kalimantan, Indonesia, using ground-based instruments -- 23. Air Pollution Caused by Deep Peatland Fire in Central Kalimantan -- 24. Chemical Speciation of PM0 Emissions from Peat Burning Emission in Central Kalimantan, Indonesia -- 25. GHG emissions estimation from Peatland fires in Indonesia - Review and Importance of Combustion Factor -- 26. Forest Fire Emissions in Equatorial Asia and Their Recent Delay Anomaly in the Dry Season -- Section III: Air Pollution Modeling and Decision Support Systems -- 27. Impact of vegetation fires on regional aerosol black carbon over South and East Asia -- 28. Detection and Modeling of South Asian Biomass Burning Aerosols from both Macro- and Micro-perspective -- 29. Remote sensing of agricultural biomass burning aerosols, gaseous compounds, long-distance transport and impact on air quality -- 30. Agricultural fires in Northeast China: Characteristics, Impacts, and Challenges -- 31. Air Pollution Modelling in Southeast Asia - An Overview -- 32. Trace gases and air quality in Northwestern Vietnam during recurrent biomass burning on the Indochina Peninsula since 0 - Field Observations and Atmospheric Simulations -- 33. Southeast Asian Transboundary Haze in the Southern Philippines, and Meteorological Drivers -- 34. An Operational Fire Danger Rating System for Thailand and Lower Mekong Region: Development, Utilization, and Experiences -- 35. Fires Hotspot Forecasting in Indonesia Using Long Short-Term Memory Algorithm and MODIS Datasets.
Keywords: Earth sciences; Natural disasters; Geographic information systems; Atmospheric science; Physical geography; Biogeography; Earth Sciences; Natural Hazards; Geographical Information System; Atmospheric Science; Earth System Sciences; Biogeosciences